Strategi Pemasaran dalam Meningkatkan Daya Saing Usaha Keripik Usus Mardha Desa Badrain Kecamatan Narmada Kabupaten Lombok Barat - Ida Mawadah; Zaenudin Mansyur; Muh. Azkar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The background of this research is the existence of sharp competition between companies, both because of the increasing number of competitors, increasing product volume and rapidly increasing technological developments. This forces companies to pay attention and know what kind of marketing strategy is implemented by the company. The focus is this study was to describe the implementation of the marketing strategy of the intestine Mardha Chips Business in increasing competitiveness and the impact of the marketing strategy implementation by the intestine Mardha Chips Business. This study used qualitative descriptive type approach. Data collection methods used were observation, interview and documentation methods. The results of this study indicate that (1) Mardha Intenstinal Chips Business used a good marketing strategy, namely by conducting market segmentation, target market, market position and marketing mix which includes product strategy, price strategy, location and distribution strategy, and promotion strategy; (2) The marketing strategy implemented by Mardha intestine Chips Business has had positive impacts including increasing sales, adding value to the family economy, prodiving satisfaction to consumers with quality product and affordable prices and expanding market share.